Analisis preferensi industri kecil berbasil teping terigu terhadap pemilihan jenis tepung terigu di Kotamadya (Preference Analysis of Wheat Flour Industries Against The Selection of Wheat Flour Brandsin Yogyakarta ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
In the low class of small scale wheat flour based industries, price attribute played the most important role in choosing wheat flour, followed by dough rising, accessibility, dough elasticity, flavour and colour. The medium class wheat flour based industries had different considerationsâ price, dough elasticity, dough rising, flavour, accessibility and colour. The price attribute had still the first consideration in choosing wheat flour in the high class of small scale industries and than followed by accessibility, dough elasticity, dough rising, flavour and colour. This research also showed, that the most preferred wheat flour brand by small scale industries based in wheat flour were Cakra Kembar (50%), Segitiga Biru (43%), Beruang Biru (2,8%), Kunci Biru (1,4%), Melati (1,4%) and Raflesia (1,4 %).